2019
DOI: 10.1186/s12955-019-1193-y
|View full text |Cite
|
Sign up to set email alerts
|

Well-being and health-related quality of life in new-generation migrant workers in Zhejiang province, China

Abstract: Background: The World Health Organization Quality of Life-BREF (WHOQOL-BREF) has generally been used for patients, few studies in migrants who move from rural to urban within one country. Many studies asserted that social isolation presents a risk to individual health. Poor social networks are associated with worse QOL. This study examined health-related quality of life (HRQOL) and social support in new-generation migrant workers and compared it with urban workers. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
3
24
2
Order By: Relevance
“…The mean score for quality of life among the study participants was 89.85 (SD=11.21). This is higher than the score reported from a previous study on new-generation migrant workers in Eastern China (mean score=62.8) [23]. Thus, Indonesian migrant workers in South Korea are considered to have a higher level of quality of life compared to migrant workers in Eastern China.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The mean score for quality of life among the study participants was 89.85 (SD=11.21). This is higher than the score reported from a previous study on new-generation migrant workers in Eastern China (mean score=62.8) [23]. Thus, Indonesian migrant workers in South Korea are considered to have a higher level of quality of life compared to migrant workers in Eastern China.…”
Section: Discussioncontrasting
confidence: 73%
“…In the present study, social support was a significant factor associated with quality of life. Xing et al [23] assessed the level of social support using WHOQOL-BREF and the Social Support Rating Scale and found that social support affected quality of life among migrant workers in Eastern China. The researchers assumed that social support of people from an individual's country of origin could be limited in urban areas because of unfriendliness and neighbourhood characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the new-generation MWs have inadequate social support and weak social network, which significantly contribute to their poorer mental health compared to the old-generation MWs [ 19 , 29 ]. Similarly, our study found migrating alone was significantly correlated with psychological distress of the new-generation MWs.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign workers may experience difficulty adapting to their new position; they might experience more work-related stress such as inadequate rest due to overtime work and inadequate medical and social security coverage provided by the employers [91]. Social relationships and networks that exist in the countryside are difficult to achieve in urban areas because of the distances and surroundings, leading to ever-decreasing social support [92,93]. To reduce work-related stress and foster interpersonal relationships in migrants, the psychology of sustainable development promotes greater connection with nature and empathy.…”
Section: Discussionmentioning
confidence: 99%